The Relationship of the Old and New Testaments - Linda Joyce; Timotius Sukarna (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
This article examines the relationship between the Old Testament (OT) and the New Testament (NT) through a qualitative approach with a literature review method. The study aims to identify theological continuities and discontinuities between the two parts of the Bible as well as outline how the narrative of God's salvation develops from the OT to the NT. The analysis was conducted by examining various primary and secondary literature from theological scholars, biblical historians and commentators. The results show that despite differences in historical context and theological development, the OT and NT have an integral and complementary relationship, especially in terms of the fulfilment of prophecy, Messianic conception, and the unfolding of God's plan of salvation. The findings are expected to enrich the understanding of contemporary Christian theology and contribute to the dialogue between the OT and NT exegetical traditions.